2022
DOI: 10.3390/agronomy12071499
|View full text |Cite
|
Sign up to set email alerts
|

Bread Wheat Productivity in Response to Humic Acid Supply and Supplementary Irrigation Mode in Three Northwestern Coastal Sites of Egypt

Abstract: Drought stress is a major factor limiting wheat crop production worldwide. The application of humic acid (HA) and the selection of the appropriate genotype in the suitable site is one of the most important methods of tolerance of wheat plants to drought-stress conditions. The aim of this study was achieved using a three-way ANOVA, the stress tolerance index (STI), the Pearson correlation coefficient (rp), and principal component analysis (PCA). Three field experiments in three sites (Al-Qasr, El-Neguilla, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…1). The results of the scree plot were harmonic with Yehia and El-Hashash [25], El-Hashash [32], El-Hashash et al [33] and El Sherbiny et al [34], who reported that there is a break in the plot that separates the meaningful components from the trivial components. Thus, most researchers would agree that PC1 and PC2 are probably meaningful.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 54%
“…1). The results of the scree plot were harmonic with Yehia and El-Hashash [25], El-Hashash [32], El-Hashash et al [33] and El Sherbiny et al [34], who reported that there is a break in the plot that separates the meaningful components from the trivial components. Thus, most researchers would agree that PC1 and PC2 are probably meaningful.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 54%
“…The biplot diagram showed how years, N treatments, and varieties all contributed to the variability of all grain yield and physiological parameters assessed. Sharp and obtuse angles between variable vectors indicate positive and negative correlation, respectively [27]. Most of the analyzed traits showed a positive association; however, they varied in terms of degree and quantity consistency.…”
Section: Principal Component Analysis (Pc)mentioning
confidence: 94%
“…Weather often played a role in the variations between years [26]. We can therefore presume that the large variations in grain yield and physiological features of bread wheat were caused by meteorological factors and genotype variability [27] as well as N treatments. Differences in genotypes can be crucial in assisting wheat breeders in creating bread wheat that is more resistant to climate change [28].…”
Section: Three-way Anovamentioning
confidence: 99%
See 2 more Smart Citations